Ownership structure and directors’ compensation disclosure in Malaysia - Esa E.B.; Zahari A.R. (World Scientific Publishing Co., 2023)
In Malaysia, the issues of corporate governance, transparency and disclosure have been the focus of researchers particularly after the economic turmoil in 1997. Weakening corporate governance in many firms is one of the factors that contributed to the 1997 Asian financial crisis. This study mainly examines how ownership structures are associated with the directors’compensation disclosure among 100 largest listed companies in Malaysia. A number of studies have looked into the ownership structure in Malaysian companies, however, none of the research has explored the issue of directors’ compensation disclosure. Disclosure and governance environment are found to be the predominant factors in enhancing firm value. Therefore, to avoid any pressure from regulatory authorities and to reduce the gap between management and investors, firms should disclose more. The study uses a directors’compensation disclosure checklist to score the items in the annual reports and multiple regression analysis to examine the association between ownership structure and the extent of directors’ compensation disclosure. The finding of this study revealed that the government ownership was positively associated and statistically significant at 1% level with the extent of directors’ compensation disclosure, while the percentage of family members on the board is negatively associated to the extent of directors’ compensation disclosure. © 2015 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.